Heavy nuclei at the end of the cosmic ray spectrum - Anchordoqui, Luis Alfredo (1999)
We provide an account of the possible acceleration of iron nuclei up to energies 300 EeV in the nearby, metally rich starburst galaxy NGC 253. It is suggested that particles can escape from the nuclear region with energies of ~1015 eV and can then be reaccelerated at the terminal shock of the galactic superwind generated by the starburst, avoiding the photodisintegration expected if the nuclei were accelerated in the central region of high photon density. We have also made estimates of the expected arrival spectrum, which displays a strong dependence on the energy cutoff at the source.